Presidential Decree Number 62 of 2023: Distortion Regulation or Acceleration Solution for Agrarian Reform? - Rahmat Ramadhani; Ida Hanifah; Farid Wajdi (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
The implementation of Presidential Decree No. 62 of 2023 has substantively attempted to integrate several regulations at technically applicable level; however, on the other hand, it still raises several problems, particularly in relation to the provision of land for agrarian reform objects, land originating from forest areas. This study aimed to analyze the implementation of Presidentialial Decree No. 62 of 2023 as the latest regulation regarding the acceleration of agrarian reform activities in Indonesia as an effort to recognize that land is the greatest source of wealth for people as ordered by the constitution. To analyze the problem, the method used is type study law normative. One of the factors inhibiting agrarian reform from seeming slow in creating just and prosperous land is the dis-harmonization of regulations, that cause legal gaps. The method used is normative legal research with a statutory regulation approach. The sectoral egos and legal gaps can be put aside and released to joint policies between related institutions, and agrarian reform can achieve its main essence; namely making land a source of the greatest prosperity for people. The results show that regulatory disharmony has narrowed the space for implementing agrarian reform. The advice given in this paper is to create an acceleration of agrarian reform that is right on target in accordance with the targets set, all implementing stakeholders must comply with the norms set out in the Presidential Decree in question. Thus, it is feared that Presidential Decree No. 62 of 2023 will become a regulatory distortion, even though its implementation aimed to provide a regulatory solution in the context of accelerating agrarian reform in Indonesia.